A revision of the South African leafhopper genus Drakensbergena Linnavuori (Hemiptera: Cicadellidae: Drakensbergeninae) - Stiller, Michael (Zootaxa, 2009)
The leafhopper genus Drakensbergena is revised. Two species are redescribed: the type-species, D. fuscovittata Linnavuori and D. ochracea Linnavuori. The following 16 species are described as new: D. armstrongi, D. austrina, D. bisulca, D. breviata, D. cuneifer, D. deorsuspina, D. festucacola, D. gigascutica, D. labeona, D. lobulata, D. longinqua, D. phaeogramma, D. prolixa, D. retrospina, D. simulata and D. spinula. Keys are provided for the identification of all the species.